THE EFFECT OF KATUK LEAF (Sauropus androgynus L. Merr) EXTRACT ON DRINKING WATER TO EGG PRODUCTION OF LOHMANN BROWN LAYING HENS AGE OF 22 – 30 WEEKS - S. H., Putri; Suasta, I M.; Bidura, I G. N. G. (Jurnal Peternakan Tropika, 2018)
This study aims find out the effect of katuk leaf ( Sauropus androgynus L. Merr) extract given into drinking water to egg production of Lohmann Brown chicken. This research was conducted in Dajan Peken Village, Tabanan Sub-district, Tabanan District for 2 months. A total of 36 Lohmann Brown chicks aged 22-30 weeks used in this study were divided into three treatments. The treatment consisted of drinking water without katuk leaf extract (Sauropus androgynus L. Merr) as control (K0), drinking water given 3% katuk leaf extract ( Sauropus androgynus ) as K1, and drinking water given 6% katuk leaf extract ( Sauropus androgynus ) as K2. The research design used was Completely Randomized Design (CRD) with six replications. The observed variables include feed consumption, water consumption, feed conversion ratio, total egg production, hen day production (HDP), egg weight and egg weight on average. In case of significant differences, then followed by multiple analysis of Duncan multiple range test. The results showed that giving the katuk leaf extract ( Sauropus androgynus ) through drinking water as much as 3% and 6% can markedly increase feed consumption, water consumption, total egg production, hen day production (HDP), egg weight and egg weight on average (P<0.05), but decreased the conversion rate of the ration (P <0.05). Based on the result of the research, it can be concluded that giving the katuk leaf extract ( Sauropus androgynus ) as much as 3% and 6% through drinking water can increase Lohmann Brown chicken egg production aged 22-30 weeks. Keywords: Sauropus androgynus L. Merr, Lohmann Brown, egg production